Biomedia and health: advantages and disadvantages in pandemic time - Regiane Cristina Duarte (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2021)
In Brazil and in the world, the experience of the years 2019 to 2021 will be marked by the coronavirus pandemic. Understanding the scenario and the pieces of information, and disseminating the knowledge become valuable strategies as a preventive measure against the virus in this pandemic. The purpose of this article is to identify evidences of the influence of social networks on health care. This article is an integrative review for a discussion on the use of biomedia in health. We show a multifaceted relationship between social networks and health, involving an intricate web of interactions that reflect on individual and community health. Therefore, having health as subject, it is important to expand access to information, critical reflection and argumentative potential for the benefit of the community. Biomedia promotes and will continue promoting communication and learning, as it empowers the individual to take care of themselves and others, and thus it minimizes the risks.